2017
DOI: 10.5194/aab-60-409-2017
|View full text |Cite
|
Sign up to set email alerts
|

Production traits, blood metabolic profile and fatty acids of meat and tallow in response to the partial replacement of soybean meal with peas in organic lambs' feed

Abstract: Abstract. The aim of this research was to investigate the production traits, blood metabolic profile and fatty acids of meat and tallow in response to the partial replacement of soybean meal with peas in lambs' feed. The research was conducted on 30 Merinolandschaf lambs of 90 days' age over 30 days. Lambs were fed with feed mixture (1000 g day −1 lamb −1 ). In the control group protein supplement was soybean meal (SC), while in the experimental groups soybean meal was partially replaced with 13 % peas (P13) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The ELS and PSC diets did not influence the proportions of C6:0, C8:0 and C10:0, fatty acids responsible for the particular sensory properties of goats´ milk (Bessa et al, 2016) and health benefits providing better digestibility of goat milk (Zenebe et al, 2014). Bernard et al (2015) found that SCFA, specifically C6:0, C8:0 and C10:0, were lowered in milk when feeding goats with 216 g/kg DM of extruded linseed in goats´ diets Contains C18:1 t7 + t8 as a minor components, 2 Contains C18:1 t10 as a minor component, 3 Contains C18:1 t12 + t13 + t14 as a minor components, 4 Contains C18:1 c14 as a minor component, 5 Contains C19:0 a minor component, 6 Contains C18:2 t9 t12 + t8 c12 + c9 t13 a minor components; SEM-standard error of mean; a,b Row means with different superscripts differ significantly at P < 0.05 Proportions of stearic (C18:0), OA, vaccenic (VA, C18:1 t11) acid and CLA remained unaffected by dietary treatments. Bernard et al (2015) determined that addition of extruded linseed in combination with fish oil may be efficient in increasing VA and CLA proportions in milk.…”
Section: Resultsmentioning
confidence: 99%
“…The ELS and PSC diets did not influence the proportions of C6:0, C8:0 and C10:0, fatty acids responsible for the particular sensory properties of goats´ milk (Bessa et al, 2016) and health benefits providing better digestibility of goat milk (Zenebe et al, 2014). Bernard et al (2015) found that SCFA, specifically C6:0, C8:0 and C10:0, were lowered in milk when feeding goats with 216 g/kg DM of extruded linseed in goats´ diets Contains C18:1 t7 + t8 as a minor components, 2 Contains C18:1 t10 as a minor component, 3 Contains C18:1 t12 + t13 + t14 as a minor components, 4 Contains C18:1 c14 as a minor component, 5 Contains C19:0 a minor component, 6 Contains C18:2 t9 t12 + t8 c12 + c9 t13 a minor components; SEM-standard error of mean; a,b Row means with different superscripts differ significantly at P < 0.05 Proportions of stearic (C18:0), OA, vaccenic (VA, C18:1 t11) acid and CLA remained unaffected by dietary treatments. Bernard et al (2015) determined that addition of extruded linseed in combination with fish oil may be efficient in increasing VA and CLA proportions in milk.…”
Section: Resultsmentioning
confidence: 99%
“…soybean, which is of genetically modified organism (GMO) origin and not competitively priced. Pumpkin seed cake, peas, sunflower seed cake (Klir et al, 2017;Antunović et al, 2017;2018 and, and recently hempseed cake have been used instead of soybean.…”
mentioning
confidence: 99%
“…Plasma BHB is a ketone body synthesized in the liver after adipose tissue catabolism, and the lack of effect of pea would confirm that the animals were not under a short-term negative energy balance [34]. Similarly, Antunović, Klir, Šperanda,Ćavar, Mioč and Novoselec [32] reported similar BHB concentrations with the inclusion of 13% and 26% pea during 30 d in organic lambs.…”
Section: Blood Metabolitesmentioning
confidence: 82%
“…These results are in line with those of Lestingi, Facciolongo, Jambrenghi, Ragni and Toteda [16] and Facciolongo, Rubino, Zarrilli, Vicenti, Ragni and Toteda [18], who reported no effect of the inclusion of up to 30% field pea during a feeding period of more than 42 days on protein and urea content in the plasma of growing lambs. In contrast, Antunović et al [32] reported a reduction of plasmatic urea when lambs were fed 13% or 26% field pea for 30 d. This reduction was related to a lower degradability of field pea protein, leading to decreased ammonia production in the rumen and, thus, a reduced urea content in plasma.…”
Section: Blood Metabolitesmentioning
confidence: 92%